Die Grundrechtskollision Ein Beitrag zu einer folgenethischen Grundrechtsdogmatik Matthias Uffer Reihe: Fundamenta Juridica Band 74 1. Auflage 2021 CC-BY-NC-ND Vollzugriff doi.org/10.5771/9783748927914 ISBN print: 978-3-8487-8415-8 - Uffer, Matthias (Fundamenta Juridica, 2021)
When fundamental rights collide, the State can be precluded from fully meeting the usual requirements of the human rights order and find itself forced to severely restrict some of the rights involved. The analysis of legal and ethical theory as well as of specific cases (e.g. shooting down of civil airplanes; "rescue torture"; force-feeding a prisoner on a hunger strike) lead the author to a decidedly consequentialist understanding of fundamental rights. The work ends with a critical discussion of reasons and criteria to be taken into account when looking for the best (i.e. least bad) resolution of conflicts of fundamental rights. (Areas: Theories of justice, dogmatics of fundamental rights, legal theory.)